2010
DOI: 10.1007/s11676-010-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Consumption and species preference for house construction wood in central highlands of Ethiopia — implications for enhancing tree growing

Abstract: A study was conducted in central Ethiopian highland in 2008 to investigate the consumption of house construction wood, the tree species preference for construction wood and the forthcoming conditions of this forest product and possible strategies for future availability. Twenty-four iron-roofed houses and twenty-eight thatch-roofed houses belonging to thirty-six farm households were investigated for types, volumes and sources of construction wood used. It was found that an average farmhouse with a floor space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For instance, over 99% of the 16,545 rural housing units standing in 2007 in Welmera district, where Menagesha forest is located, was built of wood [31]. Duguma and Hager [32] estimated that at least 39% of wood required for constructing rural housing units originated from natural forests. Computation from the national census data [31] also revealed that 99% and 27% of the households in the district rely on fuelwood and charcoal as main cooking energy, respectively.…”
Section: Contextual Factors Driving Dandd In Msf Ethiopiamentioning
confidence: 99%
“…For instance, over 99% of the 16,545 rural housing units standing in 2007 in Welmera district, where Menagesha forest is located, was built of wood [31]. Duguma and Hager [32] estimated that at least 39% of wood required for constructing rural housing units originated from natural forests. Computation from the national census data [31] also revealed that 99% and 27% of the households in the district rely on fuelwood and charcoal as main cooking energy, respectively.…”
Section: Contextual Factors Driving Dandd In Msf Ethiopiamentioning
confidence: 99%
“…procera, Afrocarpus falcatus, Olea europaea, and many other species which were rare outside the forestwere a source of many specific ES. Local communities are highly dependent on IF for firewood and charcoal (Duguma and Hager 2010), farm implements, beehives, human medicine, toothbrushes, milk-flavoring, and heritage and culture services. Thanks to these services, the IF effectively serves as a financial 'safety net' during difficult times.…”
Section: Current Distribution Of Trees and Es Across Land Use Typesmentioning
confidence: 99%
“…Houses in this study were made of walls with wooden frames, plastered mud walls and roofs made of corrugated iron sheets. The absence of traditional huts with grass thatched roofs could be partly explained by improved economic status of the community [44]. The coverage of households in the area with LLINs was found to be moderate, with every household having at least 0.5 LLINs and with total coverage being 70%.…”
Section: Discussionmentioning
confidence: 94%